A Modular Approach to the Design and Simulation of Digital Communication Systems - Soyjaudah, K. M. S.; Jahmeerbacus, M. I. (International journal of electrical engineering & education, 2000)
This paper describes an innovative approach for presenting the design and simulation of digital communication systems in a communication engineering course. Such a scheme enables students to design and implement specific parts of communication systems through group projects. This improves students' interest in the subject by addressing practical design issues from the material discussed in class.